2013
DOI: 10.1029/2012jd018658
|View full text |Cite
|
Sign up to set email alerts
|

A global view of stratospheric gravity wave hotspots located with Atmospheric Infrared Sounder observations

Abstract: [1] The main aim of this study is to find and classify hotspots of stratospheric gravity waves on a global scale. The analysis is based on a 9 year record (2003 to 2011) of radiance measurements by the Atmospheric Infrared Sounder (AIRS) aboard NASA's Aqua satellite. We detect gravity waves based on 4.3 mm brightness temperature variances. Our method focuses on peak events, i.e., strong gravity wave events for which the local variance considerably exceeds background levels. We estimate the occurrence frequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
341
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 256 publications
(389 citation statements)
references
References 84 publications
24
341
0
Order By: Relevance
“…The analysis of spatial patterns showed that the wave activity is mostly related to orographic, jet, and storm sources. The observed patterns of wave activity agree well with those reported in other climatological studies of global gravity wave activity using AIRS observations (Gong et al, 2012;Hoffmann et al, 2013Hoffmann et al, , 2014. The observed gravity wave activity is closely correlated with zonal winds at the 30 hPa level, which we attribute to the AIRS observational filter.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The analysis of spatial patterns showed that the wave activity is mostly related to orographic, jet, and storm sources. The observed patterns of wave activity agree well with those reported in other climatological studies of global gravity wave activity using AIRS observations (Gong et al, 2012;Hoffmann et al, 2013Hoffmann et al, , 2014. The observed gravity wave activity is closely correlated with zonal winds at the 30 hPa level, which we attribute to the AIRS observational filter.…”
Section: Discussionsupporting
confidence: 90%
“…We found standard errors of 29-39 % for November to February for the Northern Hemisphere and 18-21 % for May to October for the Southern Hemisphere. The spatial patterns of gravity wave activity in the lower stratosphere found here agree well with those identified by Gong et al (2012) and Hoffmann et al (2013Hoffmann et al ( , 2014Hoffmann et al ( , 2016a for the mid-and upper stratosphere.…”
Section: Temporal and Spatial Patterns Of Gravity Wave Activitysupporting
confidence: 92%
See 3 more Smart Citations